(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The relevance of the problem is significant not only in obstetrics, but also in neonatology: amniotic fluid is a biologically active environment surrounding the fetus [1], and premature rupture of membranes in the structure of causes of premature birth reaches 35–60% [2], is the cause of neonatal morbidity and mortality [3,]. According to statistics, about a million prematurely born people die from complications every year (mortality rate up to 28%); 8-10% of surviving children develop cerebral palsy, 5-8% - mental retardation, 3-5% - decompensated hydrocephalus, 2-3% - epilepsy, 3% - blindness, 1 % – hearing loss; on average, disability is about 44%The frequency of premature rupture of membranes before the onset of labor, according to various authors, varies widely from 1 to 19.8% of cases. Childbirth against the background of premature rupture of membranes is often accompanied by anomalies of labor, hypo and atonic bleeding, high rates of trauma to the soft tissues of the birth pathways, impaired uteroplacental circulation and the development of fetal hypoxia. premature rupture of amniotic fluid occurs in 3% of cases of the total number of all pregnancies. And when it’s too late in more than 50% of cases, PIOV leads to premature birth [1-3].A significant proportion of unexplained pregnancy complications may be associated with an aggressive maternal immune response towards the fetus. According to the data of domestic authors, estradiol and progesterone are involved in both specific and nonspecific reactions of the body. Thanks to the balanced action of these hormones, antifetal immune reactions are prevented and a sufficient level of antimicrobial resistance of the mother’s body is ensured [4].